(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2026)
Market of the Iraqi Stock Exchange are affected by the problem of delay in issuing financial reports by those banks. The research took banks in the regular market within the Iraqi Stock Exchange as a sample, which amounted to 20 banks. The research used two types of models, represented by the Kida model and the Sherrod model, to reveal the financial distress of banks. The survey was used to reveal the delay in issuing financial reports. The results showed that there is a weak direct relationship of 10% between financial distress and delay in issuing financial reports according to the Kida model. There was no clear relationship between financial distress and delay in issuing financial reports according to the Sherrod model. As a result of the weakness of the relationship obtained according to the two models, it can be said that there is no clear relationship between the two variables.